Analisis Keterampilan Proses Sains Siswa pada Materi Kelarutan dan Hasil Kali Kelarutan - Apriyati, Warni; Ad’hiya, Eka (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the science process skills of student groups through solubility and solubility product practicums at SMA Negeri 1 Indralaya Utara in the odd semester of the 2024/2025 academic year. The sample was determined using a purposive sampling technique. The subjects of the study consisted of 6 groups of students with 5 to 6 members each, so that the total number of participants was 34 students. This study used a descriptive method with a quantitative approach. Data were collected using observation sheets that referred to seven aspects of science process skills, namely observing, measuring, classifying, concluding, predicting, experimenting, and communicating. Data analysis was carried out descriptively by calculating the percentage of achievement of each aspect of science process skills. The results of this study indicate that the science process skills of the student group are in the very good category for the aspects of observing, measuring, concluding, predicting, and communicating, and the good category for the aspects of classifying and experimenting. The average achievement of science process skills reached 87.5%, indicating that this practicum is effective in improving students' understanding of the concept of solubility and scientific skills.